Efektivitas Modul Ajar Interaktif Berbantuan Quizlet dalam Meningkatkan Pemahaman Struktur Kalimat Bahasa Indonesia Siswa Kelas X Sekolah Menengah Kejuruan - Zihan Pratiwi Amir; Rika Kartika; Ratna Soraya (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2026)
This study aimed to analyze the effectiveness of a Quizlet-assisted interactive teaching module in improving students’ understanding of Indonesian sentence structure in response to the limited use of interactive digital learning media and students’ relatively low mastery of sentence elements in vocational Indonesian-language classrooms. The study employed a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), with the implementation and evaluation stages reported in this article. The sample consisted of 30 tenth-grade students of SMK Yapim Marelan Medan selected through purposive sampling. Data were collected through expert validation sheets, student response questionnaires, and learning outcome tests, and were analyzed using descriptive and quantitative techniques. The results showed that material and media validation reached 86% and 90%, respectively, both categorized as very feasible, while teacher assessment reached 76% (feasible) with an overall feasibility average of 84%. Student responses reached 88%, indicating that the module was highly practical. The learning outcome evaluation also demonstrated that students achieved the expected level of learning mastery after using the Quizlet-assisted module, confirming its effectiveness in strengthening students’ understanding of Indonesian sentence structure. These findings indicate that the developed module is feasible, practical, and effective, while offering a meaningful contribution to the integration of interactive digital learning media in vocational Indonesian-language instruction.